2019
DOI: 10.1080/08870446.2018.1556272
|View full text |Cite
|
Sign up to set email alerts
|

The relation between goal adjustment, goal disturbance, and mental well-being among persons with multiple sclerosis

Abstract: Objective. This study investigated the role of goal adjustment, i.e., disengaging from blocked goals and reengaging into alternative goals, in mental well-being and goal disturbance in persons with Multiple Sclerosis (MS). Design.A cross-sectional design was used with self-report data from questionnaires and Personal Project Analysis (PPA).Main outcome measures. Dependent variables were mental well-being, indicated by depression/anxiety (HADS; Hospital Anxiety and Depression Scale) and mental functioning (SF-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…As in the original study, the subscales were not found to be highly correlated with each other (.33, p < .01). Yet, a recent study by Van Damme et al (2019) found that while there was a high level of internal consistency in the goal-disengagement subscale (Cronbach's alpha was .89), it was lower for the goal reengagement subscale (Cronbach's alpha was .63).…”
Section: Introductionmentioning
confidence: 94%
“…As in the original study, the subscales were not found to be highly correlated with each other (.33, p < .01). Yet, a recent study by Van Damme et al (2019) found that while there was a high level of internal consistency in the goal-disengagement subscale (Cronbach's alpha was .89), it was lower for the goal reengagement subscale (Cronbach's alpha was .63).…”
Section: Introductionmentioning
confidence: 94%
“…In their review of the literature concerning goal adjustment in people with long-tern health conditions, such as cancer and stroke, Scobbie et al (2020) concluded that goal disengagement and goal reengagement had a positive association with recovery and well-being, although the findings for goal disengagement were mixed. In clinical studies ( Van Bost, Van Damme & Crombez, 2020 ; Van Damme et al, 2019 ) goal reengagement was positively associated with subjective QOL and life satisfaction. No effect of goal disengagement was found.…”
Section: Introductionmentioning
confidence: 94%
“…Goal reengagement is the process of finding and engaging in new, more feasible goals, and may offer the satisfaction of fulfilling new meaningful goals. The benefits of goal adjustment strategies on well-being have been shown in the context of different chronic diseases, such as cancer ( Mens & Scheier, 2016 ), multiple sclerosis ( Van Damme et al, 2019 ), and hearing loss ( Garnefski & Kraaij, 2012 ). Similar results have been found in people with an ABI ( Van Bost, Van Damme & Crombez, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A major focus of past research on TEN and FLEX is on coping with blocked goals due to aging and/or disability (e.g., multiple sclerosis; Van Damme et al, 2019). With age, goal pursuit is expected to exceed resources, and switching from tenacity to flexibility mode helps to regain an overall sense of efficacy, despite functional declines and losses (Bailly et al, 2012).…”
Section: Past Research On Ten and Flexmentioning
confidence: 99%